Entidades africanas em "troca de águas": diásporas religiosas desde o Ceará - Bandeira, Luís Cláudio Cardoso (2009)
This dissertation, inside of perspectives of the Cultural Studies, has as starting point to investigate African cultural traditions in the Ceará, with focus on nations of Candomblé linked to the cults Nagô-Vodum and Ketu, operating in Great Fortaleza. In the perspective to apprehend identity bows, historically constructed, in routes and roots , when researching the terreiros Ilê Igba Possun Azeri, Ilê Osun Oyeyé Ni Mó and Ilê Axé Oloyoba, that, according to depositions of babalorixás, yalorixás and initiates, are founding houses of these cults in Fortaleza, we sought to perceive the black presence in the State of Ceará and the religious culture developed through its brotherhoods, parties, dances, reisados, maracatus, in diversified religious cultural manifestations. Through diaspóricos circuits they had left a legacy afro-cearense that was manifested through cults afro-Brazilians gifts in great Fortaleza through the Macumba, Umbanda and Candomblé. When identifying the basic characteristics of the religions and afro-diaspóricas traditions in the Ceará, that precede candomblé, we come across with indications of memories and passages trod for mother-of-saint (yalorixás) in national and transatlantic movements. Thus, we were impelled to follow these routes that, in a constant flow and reflow of identities and religiosity, moving us to cross the black Atlantic and to disembark in Portugal, where we constructed the objective to count the history of three terreiros of candomblé, located in the Great Lisbon: Ilê Omo Orixá de Oyá Kuitéchina Oba, Ilê de Xangô Obagodô and Ilê Palace of Iemanjá. We look for to understand struggles, diasporic tensions and circuits in the instauration of the Portuguese Candomblé, beyond the expansion of afro-Brazilians religions in transnationalization processes, in a way that, such phenomenon, in portuguese lands, is intrinsically related with portuguese female migration